Pelatihan Manajemen Pengelolaan Laboratorium terhadap Guru SMA/SMK - Andi Mu'nisa; Rezki Amalia; Nani Kurnia; Hamka I (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2025)
This Community Service Activity aims to improve laboratory management competency and optimize the implementation of practicums and provide an understanding of the latest technical guidance and participants are able to manage laboratories according to standards. Participants in this activity are high school/vocational high school teachers. The method of implementation of this Community Service activity is carried out in the Biology Department laboratory. The implementation time in November 2025 is carried out for 2 days. Participants who took part in this laboratory management training are high school/vocational high school teachers. The method of implementation of this service is carried out in several stages, namely the preparation stage, and the face-to-face implementation stage. The implementation stage consists of lectures explaining material on laboratory governance and management, making preparations for preservation and direct practice in the laboratory. Direct practice in the laboratory by providing direct practical training on arranging equipment and chemicals such as making solutions, as well as occupational health and safety in the laboratory. The results of this community service activity show that participants have acquired knowledge and skills to improve teachers' abilities in managing laboratory facilities with a good managerial and technical approach. School laboratories are important places for the practice of science and technology so their management must be carried out carefully and in accordance with safety protocols.